Community-based blood pressure measurement by non-health workers using electronic devices: a validation study - Daniel D. Reidpath; Mei Lee Ling; Shajahan Yasin; Kanason Rajagobal; Pascale Allotey (Global Health Action, 2012)
Introduction: Population monitoring and screening of blood pressure is an important part of any population health strategy. Qualified health workers are expensive and often unavailable for screening. Non-health workers with electronic blood pressure monitors are increasingly used in community-based research. This approach is unvalidated. In a poor, urban community we compared blood pressure measurements taken by non-health workers using electronic devices against qualified health workers using mercury sphygmomanometers. Method: Fifty-six adult volunteers participated in the research. Data were collected by five qualified health workers, and six non-health workers. Participants were randomly allocated to have their blood pressure measured on four consecutive occasions by alternating a qualified health worker with a non-health worker. Descriptive statistics and graphs, and mixed effects linear models to account for the repeated measurement were used in the analysis. Results: Blood pressure readings by non-health workers were more reliable than those taken by qualified health workers. There was no significant difference between the readings taken by qualified health workers and those taken by non-health workers for systolic blood pressure. Non-health workers were, on average, 5–7 mmHg lower in their measures of blood pressure than the qualified health workers (95%HPD: −2.9 to −10.0) for diastolic blood pressure. Conclusion: The results provide empirical evidence that supports the practice of non-health workers using electronic devices for BP measurement in community-based research and screening. Non-health workers recorded blood pressures that differed from qualified health workers by no more than 10 mmHg. The approach is promising, but more research is needed to establish the generalisability of the results.